2012
DOI: 10.3109/08037051.2012.645336
|View full text |Cite
|
Sign up to set email alerts
|

Association of retinal microvascular caliber with blood pressure levels

Abstract: The association between different cardiovascular risk factors and hypertensive retinopathy is complex. Effective blood pressure control has a beneficial effect on the vascular changes in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
5
14
0
Order By: Relevance
“…The lack of association between CRAE and DR also has been reported in previous studies,6–8 In contrast to CRVE, CRAE has been inconsistently reported to be associated with DR in the previous studies. In accordance with what has been shown in other studies, a strong and consistent association between retinal arteriolar narrowing and hypertension has been found in the present study 21 22…”
Section: Discussionsupporting
confidence: 94%
“…The lack of association between CRAE and DR also has been reported in previous studies,6–8 In contrast to CRVE, CRAE has been inconsistently reported to be associated with DR in the previous studies. In accordance with what has been shown in other studies, a strong and consistent association between retinal arteriolar narrowing and hypertension has been found in the present study 21 22…”
Section: Discussionsupporting
confidence: 94%
“…Hypertensive retinopathy is the most common ophthalmologic manifestation of hypertension [37]. Our study results indicated that CRAE was highly correlated with MAP, consistent with numerous studies in different populations including Singaporeans [23], Japanese [38], Caucasians [2], [3], [33], [39], African-Americans [4], and multiethnic populations [5].…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies [23], [24], [35], [37], [43] have shown that CRVE is not associated with hypertension. The current study also demonstrated no significant association between CRVE and hypertension, but found that a narrow CRVE was not related to an increased PP difference, which is inconsistent with the Rotterdam Study [34].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal arteriolar narrowing has long been recognized as one of the earliest sign of hypertension secondary to chronic exposure to increased blood pressure and is inversely related to higher blood pressure levels. This finding was subsequently confirmed in multiple population-based studies [12,22,23,24,25]. A recent meta-analysis of five cross-sectional studies (including 19,633 subjects) showed that arteriolar caliber decreased by 3.07 µm [95% confidence interval (CI): 2.40-3.73 µm] for every 10-mm Hg increase in arterial blood pressure [26].…”
Section: Determinants Of Retinal Vascular Calibersmentioning
confidence: 82%
“…Of the different systemic diseases, the strongest relationship has been reported between retinal vascular calibers and hypertension [12,22,23,24,25]. Retinal arteriolar narrowing has long been recognized as one of the earliest sign of hypertension secondary to chronic exposure to increased blood pressure and is inversely related to higher blood pressure levels.…”
Section: Determinants Of Retinal Vascular Calibersmentioning
confidence: 99%